2012
DOI: 10.1590/s0101-20612012005000055
|View full text |Cite
|
Sign up to set email alerts
|

Physical and chemical characterization of the pulp of different varieties of avocado targeting oil extraction potential

Abstract: The aim of this study was to evaluate the physicochemical properties of avocado pulp of four different varieties (Avocado, Guatemala, Dickinson, and Butter pear) and to identify which has the greatest potential for oil extraction. Fresh avocado pulp was characterized by moisture, protein, fat, ash, carbohydrates and energy contents were determined. The carotenoids and chlorophyll contents were determined by the organic solvent extraction method. The results showed significant differences in the composition of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
13
1
4

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(26 citation statements)
references
References 16 publications
4
13
1
4
Order By: Relevance
“…The Collinson cultivar had higher protein content (2.1g/100g), and this value was significantly different (p ≤ 0.05) from those of the other cultivars. The protein content (1.4 to 2.1g/kg) found in the avocado pulp was similar to the data reported in other studies (Moreno et al, 2003;Gondim et al, 2005;Mooz et al, 2012).…”
Section: Fatty Acid Composition Of the Oil Extractedsupporting
confidence: 90%
“…The Collinson cultivar had higher protein content (2.1g/100g), and this value was significantly different (p ≤ 0.05) from those of the other cultivars. The protein content (1.4 to 2.1g/kg) found in the avocado pulp was similar to the data reported in other studies (Moreno et al, 2003;Gondim et al, 2005;Mooz et al, 2012).…”
Section: Fatty Acid Composition Of the Oil Extractedsupporting
confidence: 90%
“…Harvesting during less intense rainfall periods tend to produce fruits with low moisture . Moisture and lipid contents on a wet basis were similar to those reported for Hass avocados grown in Brazil, Colombia, Mexico, and Spain , from 70 to 79% and from 10 to 19%, respectively. In contrast, Tango, Carvalho, and Soares found average moisture content of 57% and a 31% lipid content for avocado grown in Brazil.…”
Section: Discussionsupporting
confidence: 78%
“…Similar data for moisture were reported for varieties commonly used for oil extraction from Fuerte and Fortuna Avocado varieties [13,38]. In addition to Hass avocados, Mooz et al [36] also worked with Guatemala, Dickinson, and Butter pear cultivars and found moisture levels exceeding 80% and low lipid contents (<10%). From previous studies of pulp pretreatment, it appears important to increase the water removal rate.…”
Section: Discussionsupporting
confidence: 59%
“…The physico-chemical composition of avocado fruit pulp and oil has been reported earlier (Turatti & Canto, 1985;Martinez et al, 1988;Lozano et al, 1993;Bora et al, 2001, Moreno et al, 2003Berasategi et al, 2012, Mooz et al, 2012Galvão et al, 2014;Indriyani et al, 2016). However, the information on the composition of volatile flavor constituents of avocado is limited.…”
Section: Introductionmentioning
confidence: 86%